Effect of dietary caffeine supplementation on the carcass composition of pacu Piaractus mesopotamicus - STEFANI GRACE S. MORAES; JONAS HENRIQUE S. MOTTA; PRISCILLA C.C. PIERRO; ANDRÉ BATISTA DE SOUZA; MARCELO F. POLESE; JOSÉ GERALDO VARGAS JÚNIOR; MANUEL V. VIDAL JÚNIOR; PEDRO PIERRO MENDONÇA (Anais da Academia Brasileira de Ciências, 2024)
Abstract Pacu (Piaractus mesopotamicus) is a fish with a high production potential in Brazil. However, one limitation is the excessive amount of ether extract in its carcass, an undesirable characteristic for the consumer. One approach to overcome this limitation is to improve carcass quality through zootechnical additives such as caffeine. The aim of this study was to evaluate the effect of supplementing the diet of pacu with caffeine on cut yield, biological indices, and carcass composition. Two hundred pacu with an initial weight of 1,687 g were used. The animals were allocated to 20 aquaculture cages of 1 m³, with 10 animals per cage. A completely randomized design with four treatments and five replicates was used. The treatments evaluated consisted of four inclusion levels of caffeine: T1 = 0.00 g; T2 = 0.16 g; T3 = 0.32 g, and T4 = 0.48 g caffeine.kg-1 of feed. The findings show that caffeine can be recommended as a diet supplement for carcass improvement of pacu, reducing the fat content and increasing the protein content of the carcass. Caffeine up to 0.32 g.kg-1 of feed can be added to the diet of pacu without affecting its performance or cut yield.